(untitled) (Baghdad Science Journal, 2006)
Factory is trotting home favorite of of Aeidid of Iraqi families since he Amta imparted to the taste of the housewife on the method of processing and preparation and the possibility of using some of the ingredients to raise the nutritional value of meat, sesame and other, but how keep Bz’zajh this product Atne storage